2020
DOI: 10.1039/c9nj04304g
|View full text |Cite
|
Sign up to set email alerts
|

A MOF functionalized with CdTe quantum dots as an efficient white light emitting phosphor material for applications in displays

Abstract: Cysteamine capped CdTe QD functionalized CP1 as a white light emitter in LED applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The incorporation of light-emitting NPs into the pores of an MOF network has also been used for the preparation of a white LEDs. Light-emitting CdTe quantum dots were prepared and immobilized in/on a Cd-based MOF network, CP1 [427] . Photoluminescence measurements showed that the CdTe quantum dot-functionalized CP1 (CdTe-CP1) showed two emission peaks at 412 and 563 nm with 330 nm excitation ( Fig.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of light-emitting NPs into the pores of an MOF network has also been used for the preparation of a white LEDs. Light-emitting CdTe quantum dots were prepared and immobilized in/on a Cd-based MOF network, CP1 [427] . Photoluminescence measurements showed that the CdTe quantum dot-functionalized CP1 (CdTe-CP1) showed two emission peaks at 412 and 563 nm with 330 nm excitation ( Fig.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…(b) CIE index diagram. Reproduced with permission from [427] . Copyright 2020 Royal Chemical Society.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy is an analytical technique that employs infrared radiation to probe the rotational or vibrational transitions of the molecules, resulting in a spectrum which is a unique fingerprint of the sample (especially in mid-IR regime), making it a versatile and effective technique for the identification of organic molecules or polymers, among others. FTIR spectroscopy is probably, together with the UV–vis/fluorescence spectroscopy, the most exploited technique for the characterization of LG@MOF materials. ,,, The simultaneous coexistence of the IR bands characteristics of the fluorophores and the MOF usually serves to identify the presence of the former and to prove the robustness of the latter upon encapsulation, all at once. ,,, Numerous and diverse examples have been reported in this sense, such as the presence of different carbon quantum dots (CDs) or metal–organic complexes (like Gaq 3 ) confined in the ZIF-8 matrix, see Figure a–d. ,,, In those systems, the FTIR spectrum is a combination of the typical IR bands of ZIF-8 and new bands of the luminescent guests like those of Gaq 3 (Figure c) or a broad band at ∼3420 cm –1 attributed to the O–H stretching vibration of the CDs (Figure d), reflecting the presence of the fluorophores and at the same time the chemical stability of the ZIF-8 after their incorporation. ,,, Similarly, the presence of inorganic perovskite nanocrystals (NCs) in different MOF hosts have been identified by the simultaneous existence of IR bands associated with the specific MOF and to the perovskite NCs, especially the bands at 2924 and 2853 cm –1 , which are the characteristics signals of the C–H symmetric and asymmetric stretching vibrations of oleylamine and oleic acid capping agents present in perovskite NCs (Figure e). , The same approach was also followed for the identification of organic dyes like fluorescein in the UiO-66 MOF, where the bands at 1638 and 1643 cm –1 were assigned to the C=O vibrations in the benzoquinone structure of the fluorescein molecule …”
Section: Characterization Methods For Lg@mof Understanding Their Capa...mentioning
confidence: 99%
“…Functionalization is an interesting approach that can be applied for MOFs due to the existence of organic linkers. The introduction of various functional groups to the organic linkers brings about numerous benefits, such as enhancement in light harvesting, linker modification to incorporate metal NPs, and improved gas capture and adsorption capabilities . Photosensitizers are molecules that are able to absorb light and transfer energy from the incident light to a nearby molecule …”
Section: Overview Of Metal Organic Framework (Mofs)mentioning
confidence: 99%